Tearfund’s Decolonisation Journey– from Jubilee to the Present - Mahdi, Bikita; Ncube, Thobekile (Christian Relief, Development, and Advocacy: The Journal of the Accord Network, 2023)
In this article, we explore what decolonisation means to the faith-based organisation Tearfund, outlining several of the organisation’s practical efforts to intentionally “reset” and decolonise its corporate culture, organisational structures, and ways of working. The theological motivation behind this organisational journey was set in motion during its Jubilee year in 2017, which sparked a renewed focus on restoring relationships, including those affected by colonialism and/or racism. The article traces an arc from 2017 to 2023, outlining organisational initiatives that aim to shift power and maximise inclusion. The purpose of so doing is to assess how the organisation’s ongoing shift from being a British charity towards becoming an authentically inclusive, global organisation has fared.